2021
DOI: 10.1111/1346-8138.16107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and treatment status of pustulotic arthro‐osteitis: A single‐center study involving 51 cases

Abstract: Pustulotic arthro‐osteitis (PAO) is a major complication of palmoplantar pustulosis (PPP). In orthopedic surgery outpatient clinics, PPP patients with osteoarticular symptoms are seen frequently, but PAO's clinical features remain not well known. To determine Japanese patients’ clinical features and treatment status with PAO, we conducted a single‐center retrospective epidemiologic survey. Clinical features, including gender, age, smoking habit, the onset pattern, interval between skin manifestation and osteoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As PsA is frequently undiagnosed among patients with PsO, this prevalence also might be lower than the true prevalence, as it is difficult for patients to link the skin eruptions on the palms and soles with the characteristic joint symptoms of PAO involving the chest wall; therefore, they might not report their joint symptoms to dermatologists 22,23 . Two previous Japanese studies reported that 59–70% of the patients had an interval less than 2 years between skin and joint symptoms, but the proportion was lower in the present study 19,20 . A higher rate of prolonged interval can also be a hindrance to linking the two symptoms.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…As PsA is frequently undiagnosed among patients with PsO, this prevalence also might be lower than the true prevalence, as it is difficult for patients to link the skin eruptions on the palms and soles with the characteristic joint symptoms of PAO involving the chest wall; therefore, they might not report their joint symptoms to dermatologists 22,23 . Two previous Japanese studies reported that 59–70% of the patients had an interval less than 2 years between skin and joint symptoms, but the proportion was lower in the present study 19,20 . A higher rate of prolonged interval can also be a hindrance to linking the two symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…Pustulotic arthro‐osteitis has been frequently studied in Japan 8,9,19,20 . However, reports involving a large number of PAO patients are relatively uncommon in other countries 15,16,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations